Compact cities sustainable urban forms for developing countries - Jenks, M. (Michael); Burgess, Rod (E. & F.N. Spon, 2000)
This new book examines and evaluates the merits and defects of compact city approaches in the context of developing countries. Issues of theory, policy and practice relating to sustainability of urban form are examined by a wide range of contributors.